Kierkegaard's Pseudonymous Authorship : A Study of Time and Self - Taylor, Mark C., 1945- (Book collections on Project MUSE., 1975)
Taylor focuses on the dramatic presentation of time and self at each state of Kierkegaard's dialectic of the stages of existence.